Application of rare earth element doped composite carrier catalyst in glycerol hydrogenolysis reaction
Through the rare earth oxide-alumina composite support catalyst supported by copper, the problem of insufficient conversion and selectivity of existing catalysts in glycerol hydrogenolysis reaction is solved, and efficient and stable preparation of 1,2-propylene glycol is achieved, reducing costs And reduce environmental pollution.
Patent Information
- Application Number
- CN202411277607.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
The conversion rate and selectivity of 1,2-propylene glycol in the glycerol hydrogenolysis reaction are insufficient, and precious metals and environmental pollution problems make it difficult to develop efficient and stable non-precious metal catalysts.
The rare earth oxide-alumina composite support catalyst was used to synthesize the copper-supported catalyst by sol-gel method and dynamic crystallization method. Cu nanoparticles were highly dispersed on the support surface, with particle size less than 2nm, pore capacity 0.3-0.5cm3/g, and surface area 100-240m2/g, the mass fraction of rare earth elements and copper in the support is optimized to improve catalytic activity.
It significantly improves the conversion rate of glycerol and the yield of 1,2-propylene glycol, has good catalyst stability, is suitable for industrial applications, reduces costs and reduces environmental pollution.
Smart Images

Figure CN119158582A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to application of a rare earth element doped composite carrier catalyst in glycerol hydrogenolysis reaction. The catalyst is composed of a rare earth oxide-alumina composite carrier loaded with active component copper. Background Art
[0002] In recent years, the increasing depletion of fossil energy and the increasingly prominent environmental pollution problems have seriously affected the sustainable development of human society. Therefore, the search for renewable clean energy has received great attention from governments and scientists around the world. In this context, biodiesel has attracted much attention due to its non-toxic, renewable, degradable and low pollution emissions. However, about 1 ton of glycerol will be produced as a by-product for every 10 tons of biodiesel produced. It can be predicted that with the rapid development of the biodiesel industry, glycerol will also be in large excess. Therefore, converting glycerol into high value-added chemicals has become one of the research hotspots in the current chemical industry. Glycerol can be produced by hydrogenolysis to produce 1,3-propylene glycol, 1,2-propylene glycol, n-propanol, isopropanol, etc. Among them, 1,2-propylene glycol is widely used as a monomer of polyester resin, antifreeze, and additives for paints, liquid detergents, cosmetics, foods, etc., so it has good economic value and market application value.
[0003] The literature [Molecular Catalysis 2021,515] reports a study on the preparation of 1,2-propylene glycol by aqueous hydrogenolysis of glycerol using a catalyst loaded with Cu and Ni on mesoporous alumina. When the catalyst feed ratio was 1, the reaction conditions were 200°C and 50 bar, the glycerol conversion rate was 67.1% and the 1,2-propylene glycol selectivity was 90.1%. Although the selectivity is high, the conversion rate is still insufficient. At the same time, the active metal content in the catalyst is high (60wt%), and the economic benefit is poor.
[0004] The paper [Chemistry–An Asian Journal 2023, 18(3)] reported a transition metal Cr oxide-doped Pt / TiO 2 The catalyst can regulate the products of glycerol hydrogenolysis. The Lewis acid sites provided by CrOx change the reaction path and make the reaction proceed in the direction of 1,2-propylene glycol. At the same time, the electron-withdrawing effect of CrOx makes the surrounding Pt positively charged, reducing its hydrogenation capacity. The maximum yield of 1,2-propylene glycol can reach 82.5%. However, considering that the catalyst contains Cr elements, it has a great pollution to the environment, and Pt is a precious metal, the catalyst cost is high, which is not conducive to large-scale industrial application. Therefore, for important reactions such as the direct preparation of propylene glycol by glycerol hydrogenolysis, it is urgent to develop new, efficient and stable non-precious metal catalysts. Summary of the invention
[0005] The invention provides a method for preparing a novel composite carrier-supported Cu-based catalyst for efficiently hydrogenolyzing glycerol to prepare 1,2-propylene glycol.
[0006] The catalyst disclosed in the present invention uses rare earth oxide-alumina as a carrier, the active component is copper, and the carrier Al 2 O 3 Total weight, Cu accounts for 1.3% of carrier Al 2 O 3 The weight percentage of the carrier is 1% to 30%, preferably 5% to 20%, and more preferably 10% to 15%; the mass fraction of the rare earth element in the carrier is 0.1% to 10%, preferably 0.5% to 4%, and more preferably 1% to 2%; copper and rare earth elements are calculated by element weight, characterized in that the active component of the catalyst is Cu nanoparticles highly dispersed on the surface of the composite carrier, the particle size distribution range is 0.5-5nm, and the average particle size is less than or equal to 2nm, and the composite carrier has the following physical properties: pore volume 0.3-0.5cm 3 / g, average pore size 4-10nm, specific surface area 100-240m 2 / g;
[0007] The catalyst preparation method comprises the following steps: firstly, the carrier is synthesized by a sol-gel method-dynamic crystallization method, and then the active component precursor solution is impregnated in the R-Al 2 O 3 On the carrier, the specific preparation process is:
[0008] 1) Add aluminum hydroxide to a dilute hydrochloric acid aqueous solution at a concentration of 1 to 20% (preferably 5% to 20%, more preferably 6.6% to 10%) at 70 to 90°C (preferably 80 to 85°C) and use a concentration of 0.05 to 0.2 M
[0009] (preferably 0.05-0.15M, more preferably 0.05-0.1M) HCl solution to adjust the pH value of the solution to between 2.5 and 3.5, prepare a sol-like liquid, and continue stirring for 60-80 minutes; the mass ratio of aluminum hydroxide to hydrogen chloride in the dilute hydrochloric acid aqueous solution is 1:2-3:1 (preferably 1:2-2:1, more preferably 1-1.5:1);
[0010] 2) transferring the formed sol-like liquid to a hydrothermal kettle, adding a rare earth element precursor aqueous solution to the hydrothermal kettle, and dynamically crystallizing the hydrothermal kettle at 150-170° C. (preferably 160° C.) for 34-38 h (preferably 36 h) at a rotation speed of 20-40 rpm (preferably 20 rpm), filtering and washing the obtained mixture, drying the solid at 80-120° C. (preferably 100° C.) for 6-10 h (preferably 8 h), and calcining at 700-900° C. (preferably 800° C.) in a muffle furnace for 2-6 h (preferably 4 h) to obtain R-Al 2O 3 The composite carrier has the following physical properties: pore volume 0.3-0.5cm 3 / g, average pore size 4-10nm, specific surface area 100-300m 2 / g;
[0011] 3) Wet impregnation of Cu precursor aqueous solution into the R-Al 2 O 3 The impregnation time is 10 to 24 hours (preferably 18 to 24 hours) on the carrier, and then dried at 80 to 90°C (preferably 85 to 90°C) for 2 to 6 hours (preferably 2 to 4 hours); if the Cu loading exceeds (is greater than or equal to) the carrier Al 2 O 3 When the mass fraction is 10%, it is necessary to adopt the process of impregnation and drying in batches, and the amount of Cu impregnation each time shall not exceed (less than or equal to) relative to Al. 2 O 3 10% of the mass, repeat the above dipping and drying operation for more than 2 batches until the required loading amount is reached;
[0012] Then, calcined at 300-500°C (preferably 300°C) for 4-6h (preferably 5h) to obtain Cu / R-Al 2 O 3 catalyst.
[0013] The Cu source in the Cu precursor solution is selected from one or more of copper nitrate, copper chloride, copper acetate, and copper ammonia complex; the rare earth precursor solution contains a lanthanum source and a cerium source, preferably a lanthanum source. The mass concentration of the Cu precursor aqueous solution is 0.043-1.29 g / mL (preferably 0.215-0.86 g / mL, more preferably 0.43-0.645 g / mL).
[0014] The lanthanum source is selected from one or more of lanthanum nitrate, lanthanum chloride and lanthanum acetate. The mass concentration of the rare earth element precursor aqueous solution is 0.0031-0.31 g / mL (preferably 0.0155-0.124 g / mL, more preferably 0.031-0.062 g / mL).
[0015] The mass fraction of La in the catalyst carrier is 0.1% to 10%, preferably 0.5% to 4%, more preferably 1% to 2%. 2 Volume percentage 50%-100% H 2 / N 2 The mixed gas is reduced (preferably 100%), the reduction temperature is 150-400° C. (preferably 200-300° C.), the reduction pressure is 0.1 MPa-5.0 MPa (preferably 1-2 MPa), and the reduction time is 0.5-5 h (preferably 2-3 h).
[0016] The activity test method for the catalyst of the present invention is as follows: in the reaction of preparing 1,2-propylene glycol by hydrogenolysis of glycerol, a high-pressure intermittent reactor, a fixed bed or a fluidized bed reactor is used, the reaction raw material is a glycerol solution, wherein the glycerol mass concentration is 1 to 30%, preferably the glycerol mass concentration is 1 to 10%; the hydrogen pressure is 0.1 to 10 MPa, preferably the hydrogen pressure is 3 to 8 MPa, more preferably 4 to 6 MPa; the reaction temperature is 150 to 250°C, preferably the reaction temperature is 180 to 220°C.
[0017] The solution is one or both of water and alcohol, preferably alcohol as the solution; wherein the alcohol is one or more of methanol, ethanol, propanol and butanol.
[0018] Compared with the prior art, the present invention can significantly improve the conversion rate of glycerol and the yield of 1,2-propylene glycol. The catalyst prepared by the method can hydrogenolyze the glycerol solution to generate 1,2-propylene glycol with high conversion rate and high selectivity under a certain hydrogen pressure and temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 10%Cu / 2%La 2 O 3 -Al 2 O 3 Catalyst long life stability diagram;
[0020] Figure 2 1) 10% Cu / Al 2 O 3 Catalyst (Comparative Example 1); 2) 10% Cu / 2% La 2 O 3 -Al 2 O 3 High-resolution spherical aberration-corrected electron microscopy image of the catalyst (Example 7);
[0021] Figure 3 10%Cu / 2%La 2 O 3 -Al 2 O 3 Distribution image of each element obtained by EDS surface scanning of the catalyst (Example 7). DETAILED DESCRIPTION
[0022] Example 1
[0023] 1 g of aluminum hydroxide was added to 10 g of a 10% by mass dilute hydrochloric acid aqueous solution at 80°C, and the pH value of the solution was adjusted to 3 using a 0.1 M HCl solution to prepare a sol-like liquid, and the stirring treatment was continued for 60 minutes;
[0024] The formed sol-like liquid was transferred to a 100 ml hydrothermal kettle, and 10 ml of a 0.062 g / ml lanthanum nitrate hexahydrate aqueous solution was added to the hydrothermal kettle. The hydrothermal kettle was subjected to dynamic crystallization at 160°C for 36 h at a speed of 20 rpm. The obtained mixture was filtered and washed, dried in an oven at 100°C for 8 h, and calcined in a muffle furnace at 800°C for 4 h to obtain 2% La 2 O 3 -Al 2 O 3 Composite support (the number in front represents La relative to Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g.
[0025] Example 2
[0026] The dissolved copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL was impregnated into 2% La 2 O 3 -Al 2 O 3 The composite carrier (prepared in Example 1) was impregnated for 24 h and dried in the shade at room temperature. The Cu mass loading was 10% relative to the composite carrier. After drying in an oven at 85 ° C for 2 h, the sample was calcined in a muffle furnace at 300 ° C for 5 h. The obtained sample was loaded into a fixed bed reactor and reduced and activated at 300 ° C in a pure hydrogen atmosphere for 2 h under a hydrogen atmosphere (1 MPa) to obtain a catalyst with a mass content of 10% Cu / 2% La. 2 O 3 -Al 2 O 3 (The number 10% before Cu represents the relative percentage of Cu to Al 2 O 3 The percentage content of Cu is 1%, the same below), Cu is evenly dispersed, the particle size distribution range is 0.54-8.55nm, and the average particle size is 1.95nm. The mass concentration of glycerol ethanol solution is 10%, the amount of catalyst is 2g, the reaction temperature is 200℃, the reaction pressure (hydrogen pressure) is 6MPa, and WHSV (glycerol ethanol solution, the same below): 1h -1 , GHSV (hydrogen, the same below): 600h -1 .
[0027] Example 3
[0028] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.0031 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 0.1% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.37cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 236m 2 / g.
[0029] Example 4
[0030] The difference from Example 2 is that the carrier is changed to 0.1% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 3), the catalyst mass content is 10% Cu / 0.1% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.53-8.47nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0031] Example 5
[0032] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.0093 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 0.3% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.37cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 235m 2 / g.
[0033] Example 6
[0034] The difference from Example 2 is that the carrier is changed to 0.3% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 5), the catalyst mass content is 10% Cu / 0.3% La 2 O 3 -Al 2 O 3, Cu is uniformly dispersed, the particle size distribution range is 0.53-8.48nm, the average particle size is 1.92nm, and the other processes and conditions are the same as those in Example 2.
[0035] Example 7
[0036] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.0155 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 0.5% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 234m 2 / g.
[0037] Example 8
[0038] The difference from Example 2 is that the carrier is changed to 0.5% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 7), the catalyst mass content is 10% Cu / 0.5% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.52-8.49 nm, the average particle size is 1.92 nm, and the other processes and conditions are the same as those in Example 2.
[0039] Example 9
[0040] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.031 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 1% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g.
[0041] Example 10
[0042] The difference from Example 2 is that the carrier is changed to 1% La 2 O 3 -Al 2 O 3Composite carrier (prepared in Example 9), the catalyst mass content is 10% Cu / 1% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.54-8.54nm, the average particle size is 1.93nm, and the other processes and conditions are the same as those in Example 2.
[0043] Embodiment 11
[0044] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.124 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 4% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-11.5nm, average pore size is 4.6nm, specific surface area is 222m 2 / g.
[0045] Example 12
[0046] The difference from Example 2 is that the carrier is changed to 4% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 11), the catalyst mass content is 10% Cu / 4% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55nm, the average particle size is 1.93nm, and the other processes and conditions are the same as those in Example 2.
[0047] Embodiment 13
[0048] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.186 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 6% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-11nm, average pore size is 4.6nm, specific surface area is 216m 2 / g.
[0049] Embodiment 14
[0050] The difference from Example 2 is that the carrier is changed to 6% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 13), the catalyst mass content is 10% Cu / 6% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.65nm, the average particle size is 1.93nm, and the other processes and conditions are the same as those in Example 2.
[0051] Embodiment 15
[0052] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.248 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 8% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-11nm, average pore size is 4.6nm, specific surface area is 207m 2 / g.
[0053] Example 16
[0054] The difference from Example 2 is that the carrier is changed to 8% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 15), the catalyst mass content is 10% Cu / 8% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.66nm, the average particle size is 1.94nm, and the other processes and conditions are the same as those in Example 2.
[0055] Embodiment 17
[0056] The difference from Example 1 is that the mass content of the lanthanum nitrate aqueous solution is changed to 0.31 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 10% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.32cm 3 / g, pore size distribution range is 2-10nm, average pore size is 4.4nm, specific surface area is 198m 2 / g.
[0057] Embodiment 18
[0058] The difference from Example 2 is that the carrier is changed to 10% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Example 17), the catalyst mass content is 10% Cu / 10% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.8nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0059] Embodiment 19
[0060] The difference from Example 1 is that the lanthanum nitrate hexahydrate solution with a mass concentration of 0.062 g / mL is replaced with a lanthanum chloride heptahydrate solution with a mass concentration of 0.053 g / mL. The other processes and conditions are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 -Cl composite carrier, the composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range 2-11.5nm, average pore size 4.8nm, specific surface area 230m 2 / g.
[0061] Embodiment 20
[0062] The difference from Example 2 is that the carrier is changed to 2% La 2 O 3 -Al 2 O 3 -Cl composite carrier (prepared in Example 19), the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 -Cl, Cu are uniformly dispersed, the particle size distribution range is 0.53-8.68nm, the average particle size is 1.96nm, and the other processes and conditions are the same as those in Example 2.
[0063] Embodiment 21
[0064] The difference from Example 1 is that the lanthanum nitrate hexahydrate solution with a mass concentration of 0.062 g / mL is replaced with a lanthanum acetate hydrate solution with a mass concentration of 0.031 g / mL. The other processes and conditions are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 -C composite carrier, the composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2.5-11.5nm, average pore size is 4.8nm, specific surface area is 232m 2 / g.
[0065] Embodiment 22
[0066] The difference from Example 2 is that the carrier is changed to 2% La 2 O 3 -Al 2 O 3 -C composite carrier (prepared in Example 21), the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 -C, Cu are uniformly dispersed, the particle size distribution range is 0.55-8.76nm, the average particle size is 1.96nm, and the other processes and conditions are the same as those in Example 2.
[0067] Embodiment 23
[0068] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 0.215 g / mL to obtain 5% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.45-8.45 nm, the average particle size is 1.92 nm, and the other processes and conditions are the same as those in Example 2.
[0069] Embodiment 24
[0070] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 0.645 g / mL to obtain 15% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.55-8.72nm, the average particle size is 1.96nm, and the other processes and conditions are the same as those in Example 2.
[0071] Embodiment 25
[0072] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 0.86 g / mL to obtain 20% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.55-8.75nm, the average particle size is 1.98nm, and the other processes and conditions are the same as those in Example 2.
[0073] Embodiment 26
[0074] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 1.075 g / mL to obtain 25% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.55-8.79 nm, the average particle size is 1.98 nm, and the other processes and conditions are the same as those in Example 2.
[0075] Embodiment 27
[0076] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 1.29 g / mL to obtain 30% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.58-8.85nm, the average particle size is 2nm, and the other processes and conditions are the same as those in Example 2.
[0077] Embodiment 28
[0078] The difference from Example 1 is that 1g of aluminum hydroxide is added to 10g of 10% diluted hydrochloric acid aqueous solution at 80°C and the temperature is changed to 70°C. The other processes and conditions are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0079] Embodiment 29
[0080] The difference from Example 1 is that 1g of aluminum hydroxide is added to 10g of 10% diluted hydrochloric acid aqueous solution at 80°C and the temperature is changed to 90°C. The other processes and conditions are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0081] Embodiment 30
[0082] The difference from Example 1 is that the mass content of dilute HCl is changed to 3.3%, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0083] Embodiment 31
[0084] The difference from Example 1 is that the mass content of dilute HCl is changed to 5%, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0085] Embodiment 32
[0086] The difference from Example 1 is that the mass concentration of dilute HCl is changed to 6.6%. The other processes are the same as in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0087] Embodiment 33
[0088] The difference from Example 1 is that the mass concentration of dilute HCl is changed to 15%, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0089] Embodiment 34
[0090] The difference from Example 1 is that the mass concentration of dilute HCl is changed to 20%, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0091] Embodiment 35
[0092] The difference from Example 1 is that the concentration of dilute HCl used to adjust the pH is changed to 0.05 M. The other processes are the same as in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0093] Embodiment 36
[0094] The difference from Example 1 is that the concentration of dilute HCl used to adjust the pH is changed to 0.15 M. The other processes are the same as in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0095] Embodiment 37
[0096] The difference from Example 1 is that the concentration of dilute HCl used to adjust the pH is changed to 0.2 M. The other processes are the same as in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0097] Embodiment 38
[0098] The difference from Example 1 is that the rotation speed is changed to 30 rpm, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0099] Embodiment 39
[0100] The difference from Example 1 is that the rotation speed is changed to 40 rpm, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0101] Embodiment 40
[0102] The difference from Example 1 is that the dynamic crystallization temperature is changed to 150°C, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 230m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0103] Embodiment 41
[0104] The difference from Example 1 is that the dynamic crystallization temperature is changed to 170°C. The other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0105] Embodiment 42
[0106] The difference from Example 1 is that the dynamic crystallization time is changed to 34h, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 230m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0107] Embodiment 43
[0108] The difference from Example 1 is that the dynamic crystallization time is changed to 38h, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0109] Embodiment 44
[0110] The difference from Example 1 is that the oven drying temperature is changed to 80°C, and the other processes are the same as Example 1 to obtain 2% La2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0111] Embodiment 45
[0112] The difference from Example 1 is that the oven drying temperature is changed to 120°C, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 231m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0113] Embodiment 46
[0114] The difference from Example 1 is that the oven drying time is changed to 6 hours, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0115] Embodiment 47
[0116] The difference from Example 1 is that the oven drying time is changed to 10 h, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 233m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0117] Embodiment 48
[0118] The difference from Example 1 is that the calcination temperature in the muffle furnace is changed to 700°C. The other processes are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.37cm 3 / g, pore size distribution range is 2-13nm, average pore size is 5.1nm, specific surface area is 235m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0119] Embodiment 49
[0120] The difference from Example 1 is that the calcination temperature in the muffle furnace is changed to 900°C. The other processes are the same as those in Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-11nm, average pore size is 4.4nm, specific surface area is 222m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0121] Embodiment 50
[0122] The difference from Example 1 is that the muffle furnace calcination time is changed to 2h, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.37cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 235m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0123] Embodiment 51
[0124] The difference from Example 1 is that the muffle furnace calcination time is changed to 6 hours, and the other processes are the same as Example 1 to obtain 2% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.34cm 3 / g, pore size distribution range is 2-11.8nm, average pore size is 4.6nm, specific surface area is 229m 2 / g, and the subsequent test conditions are the same as those in Example 2.
[0125] Embodiment 52
[0126] The difference from Example 2 is that the impregnation time is changed to 10 h, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0127] Embodiment 53
[0128] The difference from Example 2 is that the impregnation time is changed to 20 hours, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0129] Embodiment 54
[0130] The difference from Example 2 is that the oven drying temperature is changed to 80°C, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0131] Embodiment 55
[0132] The difference from Example 2 is that the oven drying temperature is changed to 90°C, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.58nm, the average particle size is 1.96nm, and the other processes and conditions are the same as those in Example 2.
[0133] Embodiment 56
[0134] The difference from Example 2 is that the oven drying time is changed to 4 h, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3, Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55nm, the average particle size is 1.95nm, and the other processes and conditions are the same as those in Example 2.
[0135] Embodiment 57
[0136] The difference from Example 2 is that the oven drying time is changed to 6 hours, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.57nm, the average particle size is 1.96nm, and the other processes and conditions are the same as those in Example 2.
[0137] Embodiment 58
[0138] The difference from Example 2 is that the calcination temperature in the muffle furnace is changed to 400°C, and the catalyst mass content is 10% Cu / 2% La. 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.62nm, the average particle size is 1.98nm, and the other processes and conditions are the same as those in Example 2.
[0139] Embodiment 59
[0140] The difference from Example 2 is that the calcination temperature in the muffle furnace is changed to 500°C, and the catalyst mass content is 10% Cu / 2% La. 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.65nm, the average particle size is 2nm, and the other processes and conditions are the same as those in Example 2.
[0141] Embodiment 60
[0142] The difference from Example 2 is that the muffle furnace calcination time is changed to 4 hours, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.53-8.55nm, the average particle size is 1.94nm, and the other processes and conditions are the same as those in Example 2.
[0143] Embodiment 61
[0144] The difference from Example 2 is that the muffle furnace calcination time is changed to 6 hours, and the catalyst mass content is 10% Cu / 2% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.59 nm, the average particle size is 1.97 nm, and the other processes and conditions are the same as those in Example 2.
[0145] Embodiment 62
[0146] The difference from Example 2 is that the reducing atmosphere is changed to 50% H 2 / N 2 , other processes and conditions are the same as in Example 2.
[0147] Embodiment 63
[0148] The difference from Example 2 is that the reducing atmosphere is changed to 60% H 2 / N 2 , other processes and conditions are the same as in Example 2.
[0149] Embodiment 64
[0150] The difference from Example 2 is that the reducing atmosphere is changed to 70% H 2 / N 2 , other processes and conditions are the same as in Example 2.
[0151] Embodiment 65
[0152] The difference from Example 2 is that the reducing atmosphere is changed to 80% H 2 / N 2 , other processes and conditions are the same as in Example 2.
[0153] Embodiment 66
[0154] The difference from Example 2 is that the reducing atmosphere is changed to 90% H 2 / N 2 , other processes and conditions are the same as in Example 2.
[0155] Embodiment 67
[0156] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction temperature was lowered to 150°C, and other processes and conditions were the same as in Example 2.
[0157] Embodiment 68
[0158] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction temperature was lowered to 200°C, and other processes and conditions were the same as in Example 2.
[0159] Embodiment 69
[0160] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction temperature was lowered to 250°C, and other processes and conditions were the same as in Example 2.
[0161] Embodiment 70
[0162] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction temperature was increased to 350°C, and other processes and conditions were the same as in Example 2.
[0163] Embodiment 71
[0164] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction temperature was raised to 400°C, and other processes and conditions were the same as in Example 2.
[0165] Embodiment 72
[0166] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation time was changed to 0.5 h, and the other processes and conditions were the same as in Example 2.
[0167] Embodiment 73
[0168] The difference from Example 20 is that 10%Cu / 2%La 2 O 3 -Al 2 O 3 The catalyst reduction activation time was changed to 1 h, and the other processes and conditions were the same as in Example 20.
[0169] Embodiment 74
[0170] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation time was changed to 3 h, and the other processes and conditions were the same as in Example 2.
[0171] Embodiment 75
[0172] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation time was changed to 4 h, and the other processes and conditions were the same as in Example 2.
[0173] Embodiment 76
[0174] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation time was changed to 5 h, and the other processes and conditions were the same as in Example 2.
[0175] Embodiment 77
[0176] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 0.1 MPa, and the other processes and conditions were the same as in Example 2.
[0177] Embodiment 78
[0178] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 0.5 MPa, and other processes and conditions were the same as in Example 2.
[0179] Embodiment 79
[0180] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 2 MPa, and the other processes and conditions were the same as in Example 2.
[0181] Embodiment 80
[0182] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 3 MPa, and the other processes and conditions were the same as in Example 2.
[0183] Embodiment 81
[0184] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 4 MPa, and the other processes and conditions were the same as in Example 2.
[0185] Embodiment 82
[0186] The difference from Example 2 is that 10% Cu / 2% La 2 O 3 -Al 2 O 3 The catalyst reduction activation pressure was changed to 5 MPa, and the other processes and conditions were the same as in Example 2.
[0187] Embodiment 83
[0188] The difference from Example 2 is that the mass concentration of the reaction substrate glycerol solution is changed to 20%, and the other processes and conditions are the same as those in Example 2.
[0189] Embodiment 84
[0190] The difference from Example 2 is that the mass concentration of the reaction substrate glycerol solution is changed to 30%, and the other processes and conditions are the same as those in Example 2.
[0191] Embodiment 85
[0192] The difference from Example 2 is that the reaction temperature is changed to 160°C, and the other processes and conditions are the same as Example 2.
[0193] Embodiment 86
[0194] The difference from Example 2 is that the reaction temperature is changed to 180°C, and the other processes and conditions are the same as Example 2.
[0195] Embodiment 87
[0196] The difference from Example 2 is that the reaction temperature is changed to 220°C, and the other processes and conditions are the same as those in Example 2.
[0197] Embodiment 88
[0198] The difference from Example 2 is that the reaction temperature is changed to 240°C, and the other processes and conditions are the same as Example 2.
[0199] Embodiment 89
[0200] The difference from Example 2 is that the reaction pressure is changed to 0.1 MPa, and the other processes and conditions are the same as Example 2.
[0201] Embodiment 90
[0202] The difference from Example 2 is that the reaction pressure is changed to 2 MPa, and the other processes and conditions are the same as Example 2.
[0203] Embodiment 91
[0204] The difference from Example 2 is that the reaction pressure is changed to 4 MPa, and the other processes and conditions are the same as Example 2.
[0205] Embodiment 92
[0206] The difference from Example 2 is that the reaction pressure is changed to 8 MPa, and the other processes and conditions are the same as those in Example 2.
[0207] Embodiment 93
[0208] The difference from Example 2 is that the reaction pressure is changed to 10 MPa, and the other processes and conditions are the same as Example 2.
[0209] Embodiment 94
[0210] The difference from Example 2 is that the reaction solution is replaced with a 10% mass concentration glycerol methanol solution, WHSV (glycerol methanol solution): 1h -1 , GHSV (hydrogen): 600h -1 , other processes and conditions are the same as in Example 2.
[0211] Embodiment 95
[0212] The difference from Example 2 is that the reaction solution is replaced with a 10% mass concentration glycerol propanol solution, WHSV (glycerol propanol solution): 1h -1 , GHSV (hydrogen): 600h -1 , other processes and conditions are the same as in Example 2.
[0213] Embodiment 96
[0214] The difference from Example 2 is that the reaction solution is replaced with a 10% mass concentration glycerol butanol solution, WHSV (glycerol butanol solution): 1h -1, GHSV (hydrogen): 600h -1 , other processes and conditions are the same as in Example 2.
[0215] Embodiment 97
[0216] The difference from Example 2 is that the copper nitrate trihydrate with a mass concentration of 0.43 g / mL is replaced by copper chloride dihydrate with a mass concentration of 0.30 g / mL, Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55 nm, and the average particle size is 1.95 nm. The other processes and conditions are the same as those in Example 2.
[0217] Embodiment 98
[0218] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced by a copper acetate monohydrate solution with a mass concentration of 0.35 g / mL, Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55 nm, and the average particle size is 1.96 nm. The other processes and conditions are the same as those in Example 2.
[0219] Embodiment 99
[0220] The difference from Example 2 is that the copper nitrate trihydrate with a mass concentration of 0.43 g / mL is replaced with a copper ammonia complex solution with a mass concentration of 0.32 g / mL, Cu is uniformly dispersed, the particle size distribution range is 0.55-8.55 nm, and the average particle size is 1.97 nm. The other processes and conditions are the same as those in Example 2.
[0221] Embodiment 100
[0222] 1 gram of aluminum hydroxide was added to 10 g of a 10% diluted hydrochloric acid aqueous solution at 80°C, and the pH value of the solution was adjusted to 3 with a 0.1M HCl solution to prepare a sol-like liquid, which was stirred for 60 minutes. The formed sol-like liquid was transferred to a 100 ml hydrothermal kettle, and 10 ml of a 0.062 g / ml hexahydrate cerium nitrate aqueous solution was added to the hydrothermal kettle. The hydrothermal kettle was subjected to dynamic crystallization at 160°C for 36 hours at a speed of 20 rpm. The obtained mixture was filtered and washed, and the solid was dried in an oven at 100°C for 8 hours, and calcined in a muffle furnace at 800°C for 4 hours to obtain 2% CeO 2 -Al 2 O 3 Composite support (the number in front represents Ce relative to Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 1.5-12nm, average pore size is 4.8nm, specific surface area is 230m2 / g.
[0223] Embodiment 101
[0224] The difference from Example 100 is that the mass concentration of the cerium nitrate aqueous solution is changed to 0.0155 g / mL, and the other processes and conditions are the same as those of Example 100 to obtain 0.5% CeO 2 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.34cm 3 / g, pore size distribution range is 1.8-12nm, average pore size is 4.8nm, specific surface area is 232m 2 / g.
[0225] Embodiment 102
[0226] The difference from Example 100 is that the mass concentration of the cerium nitrate aqueous solution is changed to 0.124 g / mL, and the other processes and conditions are the same as those of Example 100 to obtain 4% CeO 2 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 1.8-12nm, average pore size is 4.6nm, specific surface area is 225m 2 / g.
[0227] Embodiment 103
[0228] An equal volume of 0.43 g / mL copper nitrate trihydrate solution was impregnated into 2% CeO 2 -Al 2 O 3 The composite support (prepared in Example 100) was dried in the shade at room temperature, the Cu loading was 10%, and then dried in an oven at 85°C for 2h and calcined in a muffle furnace at 300°C for 5h. The obtained sample was loaded into a fixed bed reactor and reduced and activated at 300°C in a pure hydrogen atmosphere for 2h under a hydrogen atmosphere (1MPa) to obtain a catalyst with a mass content of 10% Cu / 2% CeO 2 -Al 2 O 3 , Cu is evenly dispersed, particle size distribution range: 0.55-8.65nm, average particle size 1.97nm. Glycerol ethanol solution mass concentration is 10%, catalyst amount is 2g, reaction temperature is 200℃, reaction pressure (hydrogen pressure) is 6MPa, WHSV (glycerol ethanol solution): 1h -1 , GHSV (hydrogen): 600h -1 .
[0229] Embodiment 104
[0230] The difference from Example 103 is that the carrier is changed to 0.5% CeO 2 -Al 2 O 3 Composite carrier (prepared in Example 101), the catalyst mass content is 10% Cu / 0.5% CeO 2 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.65nm, and the average particle size is 1.96nm. Other conditions are the same as those in Example 103.
[0231] Embodiment 105
[0232] The difference from Example 103 is that the carrier is changed to 4% CeO 2 -Al 2 O 3 Composite carrier (prepared in Example 102), the catalyst mass content is 10% Cu / 4% CeO 2 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.62nm, and the average particle size is 2nm. Other conditions are the same as those in Example 103.
[0233] Comparative Example 1
[0234] 1 g of aluminum hydroxide was added to 50 mL of a 10% diluted hydrochloric acid solution at 80°C, and the pH value of the solution was adjusted to 3 using a 0.1 M HCl solution to prepare a sol-like liquid, and the stirring treatment was continued for 60 minutes;
[0235] The formed sol-like liquid was transferred to a 100 ml hydrothermal kettle, and the hydrothermal kettle was subjected to dynamic crystallization at 160°C for 36 h at a rotation speed of 20 rpm. The obtained mixture was filtered, washed, dried in an oven at 100°C for 8 h, and calcined in a muffle furnace at 800°C for 4 h to obtain Al 2 O 3 The carrier has the following physical properties: pore volume 0.4cm 3 / g, pore size distribution range is 2-15nm, average pore size is 5.3nm, specific surface area is 265m 2 / g.
[0236] An equal volume of 0.43 g / mL copper nitrate solution was impregnated into the Al 2 O 3The catalyst was dried in the shade at room temperature, with a Cu loading of 10% relative to the carrier, dried in an oven at 85°C for 2h, and calcined in a muffle furnace at 300°C for 5h. The obtained sample was loaded into a fixed bed reactor and reduced and activated at 300°C in a pure hydrogen atmosphere for 2h under a hydrogen atmosphere (1MPa) to obtain a catalyst with a mass content of 10% Cu / Al. 2 O 3 , Cu is evenly dispersed, the particle size distribution range is 0.55-8.8nm, and the average particle size is 2.5nm. The mass concentration of glycerol ethanol solution is 10%, the amount of catalyst is 2g, the reaction temperature is 200℃, the reaction pressure (hydrogen pressure) is 6MPa, WHSV (glycerol ethanol solution): 1h -1 , GHSV (hydrogen): 600h -1 .
[0237] Comparative Example 2
[0238] An equal volume of 0.062 g / mL lanthanum nitrate aqueous solution was impregnated into the commercial SiO 2 The carrier was impregnated for 24 hours, dried in the shade at room temperature, dried in an oven at 85°C for 2 hours, and calcined in a muffle furnace at 500°C for 5 hours to obtain 2% La 2 O 3 -SiO 2 Composite support (the number in front represents La relative to SiO 2 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.8nm, specific surface area is 230m 2 / g.
[0239] An equal volume of 0.43 g / mL copper nitrate solution was impregnated into 2% La 2 O 3 -SiO 2 The carrier was dried in the shade at room temperature, the Cu loading was 10%, and then dried in an oven at 85°C for 2h and calcined in a muffle furnace at 300°C for 5h. The obtained sample was loaded into a fixed bed reactor and reduced and activated at 300°C in a pure hydrogen atmosphere for 2h under a hydrogen atmosphere (1MPa) to obtain a catalyst with a mass content of 10% Cu / 2% La. 2 O 3 -SiO 2 , Cu is evenly dispersed, the particle size distribution range is 0.55-8.75nm, the average particle size is 2.2nm, the mass concentration of glycerol ethanol solution is 10%, the catalyst amount is 2g, the reaction temperature is 200℃, the reaction pressure (hydrogen pressure) is 6MPa, WHSV: 1h -1 , GHSV: 600h -1 .
[0240] Comparative Example 3
[0241] An equal volume of 0.062 g / mL lanthanum nitrate aqueous solution was impregnated into a commercial
[0242] -Al 2 O 3 The carrier was impregnated for 24 hours, dried in the shade at room temperature, dried in an oven at 85°C for 2 hours, and calcined in a muffle furnace at 500°C for 5 hours to obtain 2% La 2 O 3 --Al 2 O 3 Composite support (the number in front represents La relative to -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.8nm, specific surface area is 231m 2 / g.
[0243] An equal volume of 0.43 g / mL copper nitrate solution was impregnated into 2% La 2 O 3 --Al 2 O 3 On the carrier (the specific surface area is less than 10m 2 / g), dried in the shade at room temperature, Cu loading was 10%, dried in an oven at 85°C for 2h, and then calcined in a muffle furnace at 300°C for 5h. The obtained sample was loaded into a fixed bed reactor and reduced and activated at 300°C in a pure hydrogen atmosphere for 2h under a hydrogen atmosphere (1MPa) to obtain a catalyst with a mass content of 10% Cu / 2% La. 2 O 3- -Al 2 O 3 , Cu is evenly dispersed, the particle size distribution range is 0.54-8.75nm, and the average particle size is 2.1nm. The mass concentration of glycerol ethanol solution is 10%, the amount of catalyst is 2g, the reaction temperature is 200℃, the reaction pressure (hydrogen pressure) is 6MPa, WHSV (glycerol ethanol solution): 1h -1 , GHSV (hydrogen): 600h -1 .
[0244] Comparative Example 4
[0245] The difference from Example 1 is that the mass concentration of the lanthanum nitrate aqueous solution is changed to 0.372 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 12% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.31cm3 / g, pore size distribution range is 2-11.5nm, average pore size is 4.4nm, specific surface area is 214m 2 / g.
[0246] Comparative Example 5
[0247] The difference from Example 2 is that the carrier is changed to 12% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 4), the catalyst mass content is 10% Cu / 12% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.5-8.85nm, the average particle size is 2.3nm, and the other processes and conditions are the same as those in Example 2.
[0248] Comparative Example 6
[0249] The difference from Example 1 is that the mass concentration of the lanthanum nitrate aqueous solution is changed to 0.434 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 14% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.31cm 3 / g, pore size distribution range is 1.8-11.5nm, average pore size is 4.2nm, specific surface area is 214m 2 / g.
[0250] Comparative Example 7
[0251] The difference from Example 2 is that the carrier is changed to 14% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 6), the catalyst mass content is 10% Cu / 14% La 2 O 3 -Al 2 O 3 (The number 10% before Cu represents the relative percentage of Cu to Al 2 O 3 The percentage content, %, the same below), Cu is uniformly dispersed, the particle size distribution range is 0.55-8.92nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 2.
[0252] Comparative Example 8
[0253] The difference from Example 1 is that the mass concentration of the lanthanum nitrate aqueous solution is changed to 0.496 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 16% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.30cm 3 / g, pore size distribution range is 1.8-11.3nm, average pore size is 4.0nm, specific surface area is 209m 2 / g.
[0254] Comparative Example 9
[0255] The difference from Example 2 is that the carrier is changed to 16% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 8), the catalyst mass content is 10% Cu / 16% La 2 O 3 -Al 2 O 3 (The number 10% before Cu represents the relative percentage of Cu to Al 2 O 3 The percentage content, %, the same below), Cu is uniformly dispersed, the particle size distribution range is 0.58-8.95nm, the average particle size is 2.4nm, and the other processes and conditions are the same as Example 2.
[0256] Comparative Example 10
[0257] The difference from Example 1 is that the mass concentration of the lanthanum nitrate aqueous solution is changed to 0.558 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 18% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.29cm 3 / g, pore size distribution range is 1.6-11.4nm, average pore size is 3.9nm, specific surface area is 207m 2 / g.
[0258] Comparative Example 11
[0259] The difference from Example 2 is that the carrier is changed to 18% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 10), the catalyst mass content is 10% Cu / 18% La 2 O3 -Al 2 O 3 (The number 10% before Cu represents the relative percentage of Cu to Al 2 O 3 The percentage content, %, the same below), Cu is uniformly dispersed, the particle size distribution range is 0.58-8.99nm, the average particle size is 2.5nm, and the other processes and conditions are the same as those in Example 2.
[0260] Comparative Example 12
[0261] The difference from Example 1 is that the mass concentration of the lanthanum nitrate aqueous solution is changed to 0.62 g / mL, and the other processes and conditions are the same as those in Example 1 to obtain 20% La 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.28cm 3 / g, pore size distribution range is 1.8-11.4nm, average pore size is 3.9nm, specific surface area is 205m 2 / g.
[0262] Comparative Example 13
[0263] The difference from Example 2 is that the carrier is changed to 20% La 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 12), the catalyst mass content is 10% Cu / 20% La 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-9.08nm, the average particle size is 2.6nm, and the other processes and conditions are the same as those in Example 2.
[0264] Comparative Example 14
[0265] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 1.505 g / mL to obtain 35% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.62-9.12 nm, the average particle size is 2.6 nm, and the other processes and conditions are the same as those in Example 2.
[0266] Comparative Example 15
[0267] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 1.72 g / mL to obtain 40% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.65-9.26nm, the average particle size is 2.7nm, and the other processes and conditions are the same as those in Example 2.
[0268] Comparative Example 16
[0269] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 1.935 g / mL to obtain 45% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.65-9.37 nm, the average particle size is 2.9 nm, and the other processes and conditions are the same as those in Example 2.
[0270] Comparative Example 17
[0271] The difference from Example 2 is that the mass content of the copper nitrate aqueous solution is changed to 2.15 g / mL to obtain 50% Cu / 2% La 2 O 3 -Al 2 O 3 Catalyst, Cu is evenly dispersed, the particle size distribution range is 0.68-9.55 nm, the average particle size is 3.1 nm, and the other processes and conditions are the same as those in Example 2.
[0272] Comparative Example 18
[0273] The difference from Example 2 is that the mass content of the reaction substrate glycerol solution is changed to 40%, and the other processes and conditions are the same as those in Example 2.
[0274] Comparative Example 19
[0275] The difference from Example 2 is that the mass content of the reaction substrate glycerol solution is changed to 50%, and the other processes and conditions are the same as those in Example 2.
[0276] Comparative Example 20
[0277] The difference from Example 2 is that the reaction temperature is changed to 100° C., and the other processes and conditions are the same as Example 2.
[0278] Comparative Example 21
[0279] The difference from Example 2 is that the reaction temperature is changed to 120° C., and the other processes and conditions are the same as those in Example 2.
[0280] Comparative Example 22
[0281] The difference from Example 2 is that the reaction temperature is changed to 140°C, and the other processes and conditions are the same as Example 2.
[0282] Comparative Example 23
[0283] The difference from Example 2 is that the reaction temperature is changed to 260°C, and the other processes and conditions are the same as Example 2.
[0284] Comparative Example 24
[0285] The difference from Example 2 is that the reaction temperature is changed to 280°C, and the other processes and conditions are the same as Example 2.
[0286] Comparative Example 25
[0287] The difference from Example 2 is that the reaction temperature is changed to 300° C., and the other processes and conditions are the same as those in Example 2.
[0288] Comparative Example 26
[0289] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with a praseodymium nitrate hexahydrate solution with a mass concentration of 0.062 g / mL. The other processes and conditions are the same as those of Example 100 to obtain 2% Pr 6 O 11 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.8nm, specific surface area is 228m 2 / g.
[0290] Comparative Example 27
[0291] The difference from Example 103 is that the carrier is changed to 2% Pr 6 O 11 -Al 2 O 3 Composite carrier (prepared in Comparative Example 26), the catalyst mass content is 10% Cu / 2% Pr 6 O 11 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.58nm, the average particle size is 2.2nm, and the other processes and conditions are the same as Example 103.
[0292] Comparative Example 28
[0293] The difference from Example 100 is that the hexahydrated cerium nitrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with a hexahydrated neodymium nitrate solution with a mass concentration of 0.061 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Nd 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.34cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 230m 2 / g.
[0294] Comparative Example 29
[0295] The difference from Example 103 is that the carrier is changed to 2% Nd 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 28), the catalyst mass content is 10% Cu / 2% Nd 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.56-8.75nm, the average particle size is 2.1nm, and the other processes and conditions are the same as Example 103.
[0296] Comparative Example 30
[0297] The difference from Example 100 is that the hexahydrated cerium nitrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with a hexahydrated samarium nitrate solution with a mass concentration of 0.059 g / mL. The other processes and conditions are the same as those in Example 100 to obtain a 2% Sm 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 231m 2 / g.
[0298] Comparative Example 31
[0299] The difference from Example 103 is that the carrier is changed to 2% Sm 2 O 3 -Al 2 O 3 Composite carrier (prepared in comparative example 30), the catalyst mass content is 10% Cu / 2% Sm 2 O3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.65-8.75nm, the average particle size is 2.1nm, and the other processes and conditions are the same as Example 103.
[0300] Comparative Example 32
[0301] The difference from Example 100 is that the hexahydrated cerium nitrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with hexahydrated europium nitrate with a mass concentration of 0.059 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Eu 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.36cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.9nm, specific surface area is 231m 2 / g.
[0302] Comparative Example 33
[0303] The difference from Example 103 is that the carrier is changed to 2% Eu 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 32), the catalyst mass content is 10% Cu / 2% Eu 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.75nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0304] Comparative Example 34
[0305] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with gadolinium nitrate hexahydrate with a mass concentration of 0.057 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Gd 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.35cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.7nm, specific surface area is 226m 2 / g.
[0306] Comparative Example 35
[0307] The difference from Example 103 is that the carrier is changed to 2% Gd 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 34), the catalyst mass content is 10% Cu / 2% Gd 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.57-8.76nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0308] Comparative Example 36
[0309] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with terbium nitrate hexahydrate with a mass concentration of 0.057 g / mL. The other processes and conditions are the same as those of Example 100 to obtain 2% Tb 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.4nm, specific surface area is 225m 2 / g.
[0310] Comparative Example 37
[0311] The difference from Example 103 is that the carrier is changed to 2% Tb 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 36), the catalyst mass content is 10% Cu / 2% Tb 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.57-8.77nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0312] Comparative Example 38
[0313] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with dysprosium nitrate hexahydrate with a mass concentration of 0.056 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Dy 2 O 3 -Al 2 O3 The composite carrier has the following physical properties: pore volume 0.34cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.5nm, specific surface area is 224m 2 / g.
[0314] Comparative Example 39
[0315] The difference from Example 103 is that the carrier is changed to 2% Dy 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 38), the catalyst mass content is 10% Cu / Dy 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.75nm, the average particle size is 2.2nm, and the other processes and conditions are the same as Example 103.
[0316] Comparative Example 40
[0317] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with holmium nitrate hexahydrate with a mass concentration of 0.056 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Ho 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.34cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.3nm, specific surface area is 222m 2 / g.
[0318] Comparative Example 41
[0319] The difference from Example 103 is that the carrier is changed to 2% Ho 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 40), the catalyst mass content is 10% Cu / 2% Ho 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.57-8.69nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0320] Comparative Example 42
[0321] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with erbium nitrate hexahydrate with a mass concentration of 0.055 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Er 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.32cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.2nm, specific surface area is 220m 2 / g.
[0322] Comparative Example 43
[0323] The difference from Example 103 is that the carrier is changed to 2% Er 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 42), the catalyst mass content is 10% Cu / 2% Er 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.75nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0324] Comparative Example 44
[0325] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with thulium nitrate hexahydrate with a mass concentration of 0.055 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Tm 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.3nm, specific surface area is 222m 2 / g.
[0326] Comparative Example 45
[0327] The difference from Example 103 is that the carrier is changed to 2% Tm 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 44), the catalyst mass content is 10% Cu / 2% Tm 2 O3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.58-8.76nm, the average particle size is 2.3nm, and the other processes and conditions are the same as Example 103.
[0328] Comparative Example 46
[0329] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with ytterbium nitrate hexahydrate with a mass concentration of 0.054 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Yb 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.32cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.2nm, specific surface area is 221m 2 / g.
[0330] Comparative Example 47
[0331] The difference from implementation 103 is that the carrier is changed to 2% Yb 2 O 3 -Al 2 O 3 Composite carrier (prepared by comparison 46), the catalyst mass content is 10% Cu / 2% Yb 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.56-8.74nm, the average particle size is 2.2nm, and the other processes and conditions are the same as Example 103.
[0332] Comparative Example 48
[0333] The difference from Example 100 is that the cerium nitrate hexahydrate aqueous solution with a mass concentration of 0.062 g / mL is replaced with lutetium nitrate hexahydrate with a mass concentration of 0.053 g / mL. The other processes and conditions are the same as those in Example 100 to obtain 2% Lu 2 O 3 -Al 2 O 3 The composite carrier has the following physical properties: pore volume 0.33cm 3 / g, pore size distribution range is 2-12nm, average pore size is 4.3nm, specific surface area is 220m 2 / g.
[0334] Comparative Example 49
[0335] The difference from implementation 103 is that the carrier is changed to 2% Lu 2 O 3 -Al 2 O 3 Composite carrier (prepared in Comparative Example 48), the catalyst mass content is 10% Cu / 2% Lu 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.55-8.69nm, the average particle size is 2.2nm, and the other processes and conditions are the same as Example 103.
[0336] Comparative Example 50
[0337] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with a nickel nitrate hexahydrate solution with a mass concentration of 0.56 g / mL, and the catalyst mass content is 10% Ni / 2% La 2 O 3 -Al 2 O 3 , Ni is uniformly dispersed, the particle size distribution range is 0.85-9.63nm, the average particle size is 2.9nm, and the other conditions and processes are the same as those in Example 2.
[0338] Comparative Example 51
[0339] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with an iron nitrate hexahydrate solution with a mass concentration of 0.7 g / mL, and the catalyst mass content is 10% Fe / 2% La 2 O 3 -Al 2 O 3 , Fe is evenly dispersed, the particle size distribution range is 0.86-9.78nm, the average particle size is 3nm, and the other conditions and processes are the same as those in Example 2.
[0340] Comparative Example 52
[0341] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with a manganese nitrate hexahydrate solution with a mass concentration of 0.58 g / mL, and the catalyst mass content is 10% Mn / 2% La 2 O 3 -Al 2 O 3 , Mn is uniformly dispersed, the particle size distribution range is 0.85-9.61nm, the average particle size is 2.9nm, and the other conditions and processes are the same as those in Example 2.
[0342] Comparative Example 53
[0343] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with a zinc nitrate hexahydrate solution with a mass concentration of 0.51 g / mL, and the catalyst mass content is 10% Zn / 2% La 2 O 3 -Al 2 O 3 , Zn is uniformly dispersed, the particle size distribution range is 0.85-9.65nm, the average particle size is 2.8nm, and the other conditions and processes are the same as those in Example 2.
[0344] Comparative Example 54
[0345] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with a tin nitrate solution with a mass concentration of 0.35 g / mL, and the catalyst mass content is 10% Sn / 2% La 2 O 3 -Al 2 O 3 , Sn is uniformly dispersed, the particle size distribution range is: 0.82-9.66nm, the average particle size is 2.8nm, and the other conditions and processes are the same as those in Example 2.
[0346] Comparative Example 55
[0347] The difference from Example 2 is that the copper nitrate trihydrate solution with a mass concentration of 0.43 g / mL is replaced with a lead nitrate dihydrate solution with a mass concentration of 0.20 g / mL, and the catalyst mass content is 10% Pb / 2% La 2 O 3 -Al 2 O 3 , Pb is uniformly dispersed, the particle size distribution range is 0.86-9.64nm, the average particle size is 2.8nm, and the other conditions and processes are the same as those in Example 2.
[0348] Comparative Example 56
[0349] The difference from Example 2 is that the calcination temperature in the muffle furnace is changed to 700°C, and the catalyst mass content is 10% Cu / 2% La. 2 O 3 -Al 2 O 3 , Cu is uniformly dispersed, the particle size distribution range is 0.75-12.5nm, the average particle size is 3.5nm, and the other processes and conditions are the same as those in Example 2.
[0350] Table 1 Comparison of catalytic performance of glycerol hydrogenolysis to produce 1,2-propylene glycol
[0351]
[0352]
[0353]
[0354]
[0355] *Others include small amounts of propane, methanol, ethanol, and hydroxyacetone, and the total material is conserved.
[0356] It can be seen from Examples 1-18, 100-105 and Comparative Examples 1, 4-13, 26-49 that the conversion rate of glycerol and the yield of 1,2-propylene glycol can be significantly improved by doping the carrier with rare earth element components, among which the promoting effect of La is the most significant. It can be seen from Examples 1-18 and Comparative Examples 4-13 that the mass content of La in the carrier will significantly affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. When the mass content of La in the catalyst is 2%, the yield of 1,2-propylene glycol is the highest. It can be seen from Examples 2, 23-27 and Comparative Examples 14-17, 46-51 that the properties and content of the active components have a significant effect on the reaction, among which the promoting effect of Cu is the most obvious, and the active component can be completely converted when the mass fraction is 10%, and the yield of 1,2-propylene glycol is the highest. It can be seen from Examples 28-61 and Comparative Example 56 that in the preparation process from the carrier to the catalyst, other conditions except the catalyst calcination temperature have little effect on the experimental results. The increase in calcination temperature will increase the particle size of the active component and reduce the reaction activity. It can be seen from Examples 67-71 that different reduction temperatures of the catalyst will also significantly affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. When the reduction temperature is about 200-300°C, the yield of 1,2-propylene glycol is the highest. It can be seen from Examples 62-82 that different catalyst reduction activation treatment conditions will also affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. When the reduction activation pressure is 1-2MPa and the reduction activation time is 1-2h, both the reaction activity and the cost are taken into account, which is the best reduction activation treatment condition. It can be seen from Examples 85-88 and Comparative Examples 20-25 that different reaction temperatures will also significantly affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. The conversion rate is low when the temperature is low; as the reaction temperature increases, the glycerol conversion rate is higher, but after the temperature exceeds 220°C, the high temperature will lead to an increase in by-products and a decrease in the selectivity of 1,2-propylene glycol. Therefore, 180-220°C is a more suitable reaction temperature. It can be seen from Examples 89-93 that different reaction pressures will also significantly affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. The higher the reaction pressure, the higher the conversion rate of glycerol and the yield of 1,2-propylene glycol, but the higher the pressure, the higher the investment cost. Therefore, about 4-6MPa is a more suitable reaction pressure. It can be seen from Examples 94-96 that alcohol substances, as reaction solvents, have similar effects on the reaction. It can be seen from Examples 2, 18-22, 97-99 that different types of copper and lanthanum metal salts have little effect on the reaction, but considering factors such as practicality and cost, copper nitrate is still the best choice. It can be seen from Example 2 and Comparative Examples 2-3 that different carriers will significantly affect the conversion rate of glycerol and the yield of 1,2-propylene glycol. The rare earth element-doped alumina composite carrier (R-Al 2 O 3 ) had the best glycerol conversion and 1,2-propylene glycol yield.
[0357] Embodiment 106
[0358] The stability of the catalyst is an important indicator affecting the industrial use of the catalyst. The fixed bed reactor is a commonly used operation mode in industry. Therefore, we used a fixed bed reactor to investigate the stability of the catalytic system. The specific process is as follows: 2.0 g of catalyst was filled into a stainless steel fixed bed reactor with inner and outer diameters of 12.0 mm and 20.0 mm, respectively, and a length of 430.0 mm. The particle size was 20-40 mesh. Both ends of the catalyst were filled and fixed with 8-16 mesh quartz sand and quartz wool. Before the reaction, it was reduced at 300 ° C for 2 h in a 1.0 MPa hydrogen atmosphere with a hydrogen flow rate of 20 mL / min. After the reduction was completed, the temperature was lowered to 200 ° C. A 10 wt% glycerol ethanol solution was continuously injected into the reactor through a high-pressure liquid pump. WHSV (glycerol ethanol solution): 1 h -1 , GHSV (hydrogen): 600h -1 The hydrogen gas and the glycerol ethanol solution are mixed at the inlet of the reactor and the outlet of the reactor receives a collecting device. Figure 1 As shown in the figure, glycerol can be completely converted in the fixed bed reactor, and the product is mainly 1,2-propylene glycol with a yield of 95%, and a small amount of ethylene glycol is present. After 200 hours of continuous operation, there is no significant change in the conversion rate of glycerol and the yield of 1,2-propylene glycol, indicating that the catalytic system has good stability.
Claims
1. Application of a rare earth element-doped composite carrier catalyst in glycerol hydrogenolysis reaction, characterized in that: The catalyst uses rare earth oxide-alumina as a carrier, and the active component is copper. Based on the total weight of the carrier R-Al2O3, the weight percentage of Cu in Al2O3 is 1% to 30%, preferably 5% to 20%, and more preferably 10-15%; the mass fraction of the rare earth element R (including one or two of lanthanum and cerium) in the carrier relative to Al2O3 is 0.1% to 10%, preferably 0.5% to 5%, and more preferably 1% to 2%; copper and rare earth elements are both calculated by element weight; the active component of the catalyst is Cu nanoparticles dispersed on the surface of the composite carrier, and the average particle size thereof is less than or equal to 2 nanometers, and the composite carrier has the following physical properties: pore volume 0.3 to 0.5 cm 3 / g, average pore size 4-10nm, specific surface area 100-240m 2 / g.
2. The use according to claim 1, characterized in that: The catalyst preparation process is as follows: firstly, the carrier is synthesized by a sol-gel method-dynamic crystallization method, and then the active component precursor solution is impregnated on the R-Al2O3 carrier by a wet method.
3. The use according to claim 2, characterized in that: The specific preparation process is: 1) adding aluminum hydroxide to a dilute hydrochloric acid aqueous solution at a concentration of 1 to 20% (preferably 5% to 20%, more preferably 6.6% to 10%) at 70 to 90° C. (preferably 80 to 85° C.), adjusting the pH value of the solution to between 2.5 and 3.5 using a 0.05 to 0.2 M (preferably 0.05 to 0.15 M, more preferably 0.05 to 0.1 M) HCl solution to prepare a sol-like liquid, and continuing to stir for 60 to 80 minutes; the mass ratio of aluminum hydroxide to hydrogen chloride in the dilute hydrochloric acid aqueous solution is 1:2 to 3:1 (preferably 1:2 to 2:1, more preferably 1 to 1.5:1); 2) The formed sol-like liquid is transferred to a hydrothermal kettle, and a rare earth element precursor aqueous solution is added to the hydrothermal kettle. The hydrothermal kettle is subjected to dynamic crystallization at 150-170° C. (preferably 160° C.) for 34-38 h (preferably 36 h) at a rotation speed of 20-40 rpm (preferably 20 rpm). The obtained mixture is filtered and washed, and the solid is dried at 80-120° C. (preferably 100° C.) for 6-10 h (preferably 8 h), and calcined at 700-900° C. (preferably 800° C.) in a muffle furnace for 2-6 h (preferably 4 h) to obtain an R-Al2O3 carrier. The composite carrier has the following physical properties: pore volume 0.3-0.5 cm 3 / g, average pore size 4-10nm, specific surface area 100-300m 2 / g; 3) Wet-impregnate the Cu precursor aqueous solution onto the R-Al2O3 carrier for 10 to 24 hours (preferably 18-24 hours), and then dry at 80 to 90°C (preferably 85-90°C) for 2 to 6 hours (preferably 2-4 hours); if the Cu loading exceeds (is greater than or equal to) 10% of the mass fraction of the carrier Al2O3, it is necessary to adopt a batch-by-batch impregnation and drying process, and the Cu impregnation amount each time does not exceed (is less than or equal to) 10% of the mass of Al2O3, and repeat the above impregnation and drying operation for more than 2 batches until the desired loading is reached; Then, the catalyst is calcined at 300-500°C (preferably 300°C) for 4-6h (preferably 5h) to obtain a Cu / R-Al2O3 catalyst.
4. The use according to claim 3, characterized in that: The Cu source in the Cu precursor solution is selected from one or more of copper nitrate, copper chloride, copper acetate, and copper ammonia complex; the mass concentration of the Cu precursor aqueous solution is 0.043-1.29 g / mL (preferably 0.215-0.86 g / mL, more preferably 0.43-0.645 g / mL); The rare earth precursor solution contains one or more of a lanthanum source and a cerium source; preferably one or more of a lanthanum source; the mass concentration of the rare earth element precursor aqueous solution is 0.0031-0.31 g / mL (preferably 0.0155-0.124 g / mL, more preferably 0.031-0.062 g / mL).
5. The use according to claim 4, characterized in that: The lanthanum source is selected from one or more of lanthanum nitrate, lanthanum chloride and lanthanum acetate.
6. The use according to any one of claims 1 to 5, characterized in that: Before use, the catalyst is reduced with a H2 / N2 mixed gas or H2 containing 50% to 100% (preferably 100%) H2 by volume, the reduction temperature is 150 to 400°C (preferably 200 to 300°C), the reduction pressure is 0.1MPa to 5.0MPa (preferably 1.0 to 2.0MPa), and the reduction time is 0.5 to 5h (preferably 2 to 3h).
7. The use according to any one of claims 1 to 6, characterized in that: The catalyst is used in the reaction of preparing 1,2-propylene glycol by hydrogenolysis of glycerol. The reaction is carried out in a high-pressure intermittent reactor, a fixed bed or a fluidized bed reactor. The reaction raw material is a glycerol solution, wherein the mass concentration of glycerol is 1-50%, preferably the mass concentration of glycerol is 1%-20%; the hydrogen pressure is 0.1-10MPa, preferably the hydrogen pressure is 3-8MPa, more preferably 4-6MPa; the reaction temperature is 150-250°C, preferably the reaction temperature is 180-220°C.
8. The use according to claim 7, characterized in that: The solution is one or two of water or alcohol, preferably alcohol as the solution; wherein the alcohol is one or more of methanol, ethanol, propanol and butanol.
